2007
DOI: 10.1177/0305735607077834
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and nature of imagined music in the everyday lives of music students

Abstract: `Musical imagery' is the experience of imagining music in the `mind's ear'. A study was conducted to explore the prevalence and nature of musical imagery for music students in everyday life, using experience-sampling methods (ESM). As a group, music students reported that imagining music was a very frequent form of musical experience. Participants reported individual variation in their imagery experience but also common differences between the strength of imagery for different musical dimensions. For instance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
169
6
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(200 citation statements)
references
References 9 publications
17
169
6
8
Order By: Relevance
“…But as Berntsen and her colleagues have argued, reexperiencing may be a component of both voluntary and involuntary memories (Hall & Berntsen, 2008;Rasmussen & Berntsen, 2009). Because people also reexperience many music features when they intentionally imagine music (Bailes, 2007;Halpern, 1988a;Halpern, 1988b;Levitin, 1994;Lucas et al, 2010), reexperiencing may be a feature of conscious experience rather than intrusive thoughts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But as Berntsen and her colleagues have argued, reexperiencing may be a component of both voluntary and involuntary memories (Hall & Berntsen, 2008;Rasmussen & Berntsen, 2009). Because people also reexperience many music features when they intentionally imagine music (Bailes, 2007;Halpern, 1988a;Halpern, 1988b;Levitin, 1994;Lucas et al, 2010), reexperiencing may be a feature of conscious experience rather than intrusive thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Having a song stuck in your head is a commonly experienced intrusive thought that occurs frequently for many people. The phenomenon has been labeled many things: an earworm (Halpern & Bartlett, 2011;Kellaris, 2008;Levitin, 2006), imagined music (Bailes, 2007), involuntary semantic memories (Kvavilashvili & Mandler, 2004), and involuntary musical imagery (Liikkanen, 2008(Liikkanen, , 2012aSacks, 2007). To make explicit the connection to other forms of intrusive thoughts, we refer to the experience as an intrusive song.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the music being listened to, much of the existing research on everyday listening has employed a relatively short list of predetermined musical categories (Bailes, 2007;North et al 2004;Sloboda et al, 2001). North et al (2004) reported frequencies with which specific styles were heard in music episodes.…”
Section: Introductionmentioning
confidence: 99%